Peningkatan Ketrampilan Smash Kendeng pada Permainan Sepak Takraw Siswa Sekolah Dasar - Aji, Tri (Universitas Negeri Semarang, 2014)
This Research is executed in elementary school of SDN 04 Karangtalun Cilacap by sample of man students, amounting to 16 people. From perception result of performed within three the cycle seen that happened by the uplifting of movement skills, this matter is proven by result analyze the data which have been collected. Movement Skill of cycle I has been improved from 25 % becoming 42%. At cycle of II of movement skill has been improved from 42% becoming 57%. While in cycle III has been improved from 57% becoming 78%. The result indicate that the indicator is reached by 75% students have owned the expected movement skill. Therefore, the improvement skills are able to increase the based movement skills of sepak takraw game in students of elementary school in Cilacap.